2016
DOI: 10.1093/icesjms/fsw058
|View full text |Cite
|
Sign up to set email alerts
|

Estimating and mitigating the discard mortality of Atlantic cod (Gadus morhua) in the Gulf of Maine recreational rod-and-reel fishery

Abstract: In recent years, the recreational contribution to the total catch of Atlantic cod (Gadus morhua) in the Gulf of Maine (GOM) has increased with recreational discards outnumbering recreational landings by 2:1. However, the discard mortality (DM) rate of cod released in the recreational fishery remains poorly understood, thus contributing to the uncertainty in stock assessments and fishery management plans. The current study examined the capture-related factors most detrimental to cod DM in the GOM recreational r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(103 citation statements)
references
References 44 publications
4
98
1
Order By: Relevance
“…Three terminal tackle types were selected for capturing Haddock due to previous survey results (Table S.1; Capizzano et al. ) and industry input, specifically two baited‐hook setups (J‐ and circle hooks) and one jig and teaser setup (treble‐hook jig) (Figure S.1). Because anglers varied in experience level (as quantified using a questionnaire), efforts were made to remove angling and capture biases that would interfere with the interpretation of study results.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three terminal tackle types were selected for capturing Haddock due to previous survey results (Table S.1; Capizzano et al. ) and industry input, specifically two baited‐hook setups (J‐ and circle hooks) and one jig and teaser setup (treble‐hook jig) (Figure S.1). Because anglers varied in experience level (as quantified using a questionnaire), efforts were made to remove angling and capture biases that would interfere with the interpretation of study results.…”
Section: Methodsmentioning
confidence: 99%
“…Equal tackle‐specific fishing effort (i.e., amount of time anglers used bait versus jigs) was also maintained throughout the study to ensure representative samples across angler experience levels, tackle types, and fishing trips (Capizzano et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because barotrauma was one of the highly significant factors for the mortality of released fish (Bartholomew and Bohnsack, 2005), a 11.2% C&R mortality for cod caught by charter boats in the North Sea is possibly conservative. Capizzano et al (2016) studied the C&R mortality of cod in the Gulf of Maine and found an average mortality rate of 16.5%. We propose the mean between the two studies, resulting in 14%.…”
Section: Codmentioning
confidence: 99%